Women migrant workers’ (WMWS) deskilling [version 2; peer review: 1 approved, 2 approved with reservations] - Marie Ruiz; Stellamarina Donato (Open Research Europe)
Women are key actresses in sending and receiving countries’ developments, and their contributions includes social and financial remittances, education and the transmission of social and cultural values (United Nations, 2006). Despite, women migrants’ undeniable contributions, they too often undergo deskilling, a process defined as the employment of workers in a different field or below their qualifications. The factors influencing deskilling include the lack of recognition of skills and qualifications, difficult access to information and employment opportunities, lack of support in the destination country and linguistic barriers. Migration can impact the social mobility of women migrants, yet not always positively (Nowicka, 2012). In the labour market, women migrants are generally disadvantaged because of occupational gender segregation, the lack of network support and childcare responsibilities (EU Commission, 2022), with higher risks of deskilling and downward social mobility. The objective of the brief is to shed light on WMWs’ deskilling and explore the impact of gender and ethnicity in labour segmentation, de-emancipation being a consequence of WMWs’ deskilling and overrepresentation in reproductive unskilled jobs.